Spatial Variation in Pelagic Wildlife Assemblages in the Ascension Island Marine Protected Area: Implications for Monitoring and Management - Thompson, Christopher D. H.; Meeuwig, Jessica J.; Brown, Judith; Richardson, Andrew J.; Friedlander, Alan M.; Miller, Peter I.; Weber, Sam B. (Frontiers in Marine Science, 2021)
Bathymetric features such as islands and seamounts, as well as dynamic ocean features such as fronts often harbour rich marine communities. We deployed mid-water baited remote underwater video systems on three expeditions in Ascension Island’s Exclusive Economic Zone (EEZ), surveying the waters associated with six different bathymetric and dynamic ocean features: Ascension Island, two shallow seamounts (summits ≤ 101 m), one deeper seamount (summit > 250 m), apparent fronts, and haphazardly sampled open ocean areas. At Ascension Island, the pelagic assemblage consisted of a moderate proportion of predators and a diverse range of other taxa, including turtles, dolphins, and large non-piscivores. At the two shallow seamounts, sharks, tunas, billfish, and other large pelagic predators formed the vast majority of the assemblage, contributing > 99.9% of biomass and > 86% of abundance. At the deeper seamount, the pelagic community was comparatively depauperate, however the functional composition of its assemblage indicated some similarities to the shallow seamounts. Apparent fronts did not significantly differ from random offshore sites for metrics such as total abundance and taxonomic richness. However, they harboured assemblages with more abundant sharks, tunas, and large piscivores than random ocean open locations and these differences may be driven by certain front-associated species. Our results illustrate that pelagic assemblages vary markedly among different physical and oceanographic features and that seamounts appear particularly important for pelagic predators. The diversity and abundance of the assemblage, as well as the threatened status of many of the species observed, serve to highlight the conservation value of the Ascension Island EEZ. Our results also provide important baseline information of pelagic wildlife assemblages against which the performance of the recently implemented Ascension Island Marine Protected Area can be evaluated.